European Experience in Regulating Human Right to Free Secondary Legal Aid (Bulletin of Kharkiv National University of Internal Affairs, 2019)
The author has analyzed the opinions of scholars on the necessity of introducing the European experience of regulating human right to free secondary legal aid into the national system of protecting human rights. It has been proved that the experience of the European countries is the key to creating the institutional and regulatory base necessary for providing free legal aid, ensuring the financial capacity and stability of the functioning of human rights protection system in Ukraine.There author has defined two key conditions for ensuring human right to free legal aid: 1) the condition of the state or the “poverty and need test”, which is based on a financial criterion, which allows to determine the lack of sufficient funds to pay for legal aid of a lawyer; 2) a condition of the essence or a “test for the interest of justice” that links the provision of free legal aid to the requirements of justice.On the basis of the analysis of the basic normative acts of the European countries and the judgments of the European Court of Human Rights, the author has distinguished basic criteria of the necessity of rendering a person free legal aid: 1) demand of interests of justice; 2) the complexity of the court case; 3) the need for the services of a lawyer in regard to the particular circumstances of the case; 4) financing of legal aid by the state.